Evaluation of New Cotton Ranges According to Their Indices Quality of Fiber - Boltabaev, H. A. (American Journal of Biodiversity, 2026)
The article presents the results of the analysis obtained during the testing of the fiber quality in the competitive variety testing of cotton lines, and provides an assessment of the fiber micronaire, strength, length, uniformity, short fiber index, relative elongation, contamination, and the number of defects. To solve the assigned tasks, scientific research work is being carried out in a certain volume at the Namangan Experimental Station of the "Research Institute of Selection, Seed Production and Agrotechnology of Cotton Cultivation". A number of new lines were created, which were compared in terms of valuable economic traits and technological indicators of fiber quality with standard cotton varieties. The experiments were conducted based on the "Instructions for state variety testing of agricultural crops". Based on the results of analyses obtained in competitive tests of the fiber quality of new cotton lines, it was revealed that the highest results for 4 technological indicators (Str, Len, Unf, SFL) were obtained on lines 158 and 162. These lines fully meet all the requirement.